Navigating pressured ice: Risks and hazards for winter resource-based shipping in the Canadian Arctic. (1st March 2017) - Mussells, Olivia; Dawson, Jackie; Howell, Stephen
Abstract: Year-round shipping is becoming common in the Canadian Arctic, a region rich in increasingly accessible natural resources. Currently, an average of two round-trip winter voyages (four single transits) (January, February, March) are made annually through the Hudson Strait to service the Raglan nickel mine in Deception Bay, Quebec. During these winter transits it is common for vessels to encounter pressured ice and become beset (stuck) for hours to days at a time. Pressured (or ridged) ice is one of the most challenging navigational hazards in the Arctic as it is difficult to predict or even detect until a vessel comes into direct contact with it. Using ship logs from 33 one-way winter transits through the Hudson Strait during winter months between 2005 and 2014, we evaluate the temporal and spatial frequency of vessel besetment events and relate these events with satellite based imagery of the region in order to examine the potential of satellite-based detection of ridges for the possible future development of real-time or prediction analytics for ridging events. Results indicate that on average the ship was beset 42% of each transit while in the Hudson Strait and often became beset in areas and times of the year associated with high ridge densities. These findings provide a basis for improving observation and prediction of hazardous ice conditions through the use satellite imagery and historic analysis of besetting events, though additional research is needed. Highlights: Pressured sea ice and ridges are hazardous to ships travelling in the Canadian Arctic and can cause them to become beset. Study inventoried shipping besetting events from 33 transits through the Hudson Strait, 2005–2014. Vessel was beset on average 42% of time while in the Hudson Strait. Association between besetting events and ridges identified in satellite imagery is promising for ship navigation.